Environmentally friendly high corrosion resistance zinc-aluminum coating for metal components and preparation method thereof

By adding modified epoxy resin and modified filler to zinc-aluminum coatings, the formulation and preparation method are optimized, and the problem of insufficient protective effect of zinc-aluminum coatings in harsh environments is solved, and efficient corrosion and waterproof performance is achieved, which meets the Comprehensive performance requirements of metal components.

CN118813123BActive Publication Date: 2024-12-20JILIN JIANZHU UNIVERSITY +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411251243.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-07
Publication Date
2024-12-20
Estimated Expiration
2044-09-07

AI Technical Summary

Technical Problem

The existing zinc-aluminum coatings have limited protective effects in harsh environments and are harsh in construction conditions, making it difficult to meet performance requirements such as high temperature stability, chemical stability, waterproofness and aging resistance.

Method used

It adopts environmentally friendly high-corrosion zinc-aluminum coatings for metal components, and the formula includes zinc powder, aluminum powder, modified epoxy resin and modified fillers. By optimizing the formulation and preparation method, an efficient anti-corrosion and waterproof coating is formed.

Benefits of technology

It achieves good corrosion resistance and environmental protection performance, and maintains the high temperature, chemical stability, waterproofness and aging resistance of the paint, meeting the comprehensive performance requirements of metal components.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present application relates to the field of zinc-aluminum coatings, and in particular to environmentally friendly and highly anti-corrosion zinc-aluminum coatings for metal components and their preparation methods. Environmentally friendly and highly anti-corrosion zinc-aluminum coatings for metal components, in parts by mass, have the following raw materials: 20 to 40 parts of zinc powder, 10 to 25 parts of aluminum powder, 5 to 15 parts of wetting agent, 1 to 3 parts of dispersant, 10 to 20 parts of resin material, 0.5 to 1 part of defoaming agent, 10 to 15 parts of modified filler, and 40 to 55 parts of solvent. The environmentally friendly and highly anti-corrosion zinc-aluminum coating for metal components prepared in the present application has good anti-corrosion and environmental protection properties, and at the same time retains excellent coating waterproofing, high temperature / chemical stability, aging resistance, wear resistance and other properties, and obtains good comprehensive performance, effectively meets the performance requirements of existing metal component products for zinc-aluminum coatings, and has very excellent application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of zinc-aluminum coatings, and in particular to an environmentally friendly and highly anti-corrosion zinc-aluminum coating specially used for metal components and a preparation method thereof. Background Art

[0002] Zinc-aluminum coatings are commonly used for anti-corrosion treatment of metal surfaces, especially for protecting steel structures in harsh environments. This type of coating usually contains zinc powder and aluminum powder as the main anti-rust ingredients. The development of the technical solution of zinc-aluminum coatings mainly stems from the demand for high-efficiency anti-corrosion materials in the application field. Although traditional anti-corrosion measures such as hot-dip galvanizing are effective, their protective effect is limited in some specific environments, and the construction conditions are relatively harsh. In order to overcome these problems, researchers have developed a variety of zinc-aluminum-based composite coatings that can provide better anti-corrosion performance.

[0003] Existing zinc-aluminum coatings usually include a mixture of zinc powder and aluminum powder, which can be made into anti-corrosion coatings with synergistic effects. Zinc powder can provide sacrificial anode protection, while aluminum powder helps to form a dense protective layer. The combination of the two can significantly improve the corrosion resistance of the coating. In addition to metal powder, the coating also needs a good film-forming substance to ensure its adhesion and weather resistance. Commonly used film-forming substances include epoxy resin, polyurethane, etc., which can form a solid protective film on the metal surface. However, with the increasing requirements for zinc-aluminum coatings, especially for the high temperature stability, chemical stability, water resistance, aging resistance and wear resistance of zinc-aluminum coatings, the demand is increasing.

[0004] Therefore, in order to solve the above problems, the present application provides an environmentally friendly and highly anti-corrosion zinc-aluminum coating for metal components and a preparation method thereof. The environmentally friendly and highly anti-corrosion zinc-aluminum coating for metal components prepared in the present application has good anti-corrosion and environmental protection properties, and at the same time retains excellent coating waterproofing, high temperature / chemical stability, aging resistance, wear resistance and other properties, and obtains good comprehensive performance, effectively meets the performance requirements of existing metal component products for zinc-aluminum coatings, and has very excellent application prospects. Summary of the invention

[0005] In order to solve the above problems, the first aspect of the present application provides an environmentally friendly and highly anti-corrosion zinc-aluminum coating specially used for metal components. The raw materials are, by mass: 20 to 40 parts of zinc powder, 10 to 25 parts of aluminum powder, 5 to 15 parts of wetting agent, 1 to 3 parts of dispersant, 10 to 20 parts of resin material, 0.5 to 1 part of defoaming agent, 10 to 15 parts of modified filler, and 40 to 55 parts of solvent.

[0006] As a preferred solution, the mass ratio of the zinc powder, aluminum powder and modified filler is (25-35): (12-18): (11-15).

[0007] As a preferred solution, the mass ratio of the zinc powder, aluminum powder and modified filler is (28-32): (14-16): (13-15).

[0008] As a preferred solution, the mass ratio of the wetting agent, the resin material and the modified filler is (6-14): (15-20): (11-15).

[0009] As a preferred solution, the mass ratio of the wetting agent, the resin material and the modified filler is (8-12): (16-18): (13-15).

[0010] As a preferred solution, the zinc powder is flaky zinc powder.

[0011] As a preferred solution, the thickness of the flaky zinc powder is 0.2-0.4 μm; and the average diameter of the flaky zinc powder is 5-15 μm.

[0012] As a preferred solution, the thickness of the flaky zinc powder is 0.25-0.35 μm; and the average diameter of the flaky zinc powder is 8-12 μm.

[0013] As a preferred solution, the aluminum powder is flake aluminum powder.

[0014] As a preferred solution, the thickness of the flaky aluminum powder is 0.15-0.3 μm; the average diameter of the flaky aluminum powder is 10-20 μm.

[0015] As a preferred solution, the thickness of the flaky aluminum powder is 0.15-0.2 μm; the average diameter of the flaky aluminum powder is 12-16 μm.

[0016] As a preferred solution, the wetting agent is a composition of coconut oil based betaine and cetearyl alcohol polyoxyethylene ether.

[0017] As a preferred embodiment, the mass ratio of the coconut betaine to the cetearyl alcohol polyoxyethylene ether is (1-1.5): (3-4).

[0018] As a preferred solution, the mass ratio of the coconut betaine to the cetearyl alcohol polyoxyethylene ether is (1-1.2): (3-3.5).

[0019] As a preferred solution, the dispersant is at least one of polyethylene glycol, polycarboxylate, polyamide wax, and modified siloxane.

[0020] As a preferred solution, the dispersant is polyethylene glycol.

[0021] As a preferred solution, the resin material is a modified epoxy resin; the preparation method of the modified epoxy resin comprises the following steps: S1: decompressing and dehydrating the epoxy resin for 2 to 4 hours at 120 to 125°C to ensure that the moisture content of the epoxy resin is ≤0.3wt%, and cooling to obtain the dehydrated epoxy resin; S2: after decompressing and dehydrating, placing the epoxy resin in a toluene solvent, heating it to 70 to 80°C and stirring evenly, then adding aminosiloxane, glutaric anhydride and triethylamine, heating it to 90 to 110°C and reacting it for 3 to 5 hours; S3: after the reaction is completed, adding amylopectin and a silane coupling agent, cooling it to 60 to 65°C and keeping it warm for 1.5 to 2 hours, and after the reaction is completed, naturally cooling the product to room temperature and centrifuging it, washing it with deionized water for 2 to 3 times, and then drying it in a vacuum oven to constant weight to obtain the product.

[0022] As a preferred solution, the aminosiloxane is γ-aminopropyltriethoxysilane or 3-aminopropylmethyldiethoxysilane.

[0023] As a preferred solution, the epoxy resin is a bisphenol A epoxy resin; the epoxy equivalent of the bisphenol A epoxy resin is 160-190 g / eq.

[0024] As a preferred solution, the mass ratio of the epoxy resin, aminosiloxane, glutaric anhydride and triethylamine is (20-25): (1-1.5): (3-5): (0.2-0.4).

[0025] As a preferred solution, the mass ratio of the epoxy resin, pullulan and silane coupling agent is (20-25): (2-2.5): (0.6-0.8).

[0026] As a preferred solution, the viscosity of the modified epoxy resin is 3000-6000 cPs at 25°C.

[0027] As a preferred solution, the viscosity of the modified epoxy resin is 4500-5500 cPs at 25°C.

[0028] The modified epoxy resin added in this application can not only effectively improve the construction speed of the coating film layer, but also effectively improve the corrosion resistance, stability and water resistance. The added modified epoxy resin can effectively form a strong intermolecular effect on the modified filler during the construction process of the coating, thereby serving as an excellent flow carrier, and can also greatly enhance the positional stability of the modified filler in the coating system by intermolecular action after the coating is cured, thereby effectively ensuring the overall stability and water resistance, and the modified epoxy resin can react the amino group of the siloxane while forming a polyhydroxy system, thereby forming a good hydrogen bonding effect inside the coating system, thereby strengthening the overall coating density and internal connection force, thereby obtaining better and excellent comprehensive performance.

[0029] As a preferred solution, the defoaming agent is at least one of silicone defoaming agents.

[0030] As a preferred scheme, the preparation method of the modified filler includes the following steps: S1: adding a mixture of graphite and silicon dioxide to a DMF solvent, adding succinic anhydride, a titanate coupling agent and triethylamine, heating to 60-65°C and keeping warm for 3-3.5 hours; S2: centrifuging the S1 product to obtain pretreated particles, washing and drying the pretreated particles, adding them to a toluene solvent, and adding zinc nitrate at the same time, heating to 50-55°C, stirring at 100-120rpm for 30-40min, adding a toluene solution of dimethylimidazole during the process, and then heating to 60-65°C and stirring at 40-60rpm for 2.5-3.5h. After the reaction is completed, centrifuging and filtering, washing the product with deionized water and vacuum drying, the product is obtained.

[0031] As a preferred solution, the mass ratio of graphite, silicon dioxide, succinic anhydride, titanate coupling agent and triethylamine is (3-3.5): (0.4-0.6): (1-1.5): (0.3-0.4): (0.05-0.15).

[0032] As a preferred solution, the mass ratio of zinc nitrate and dimethylimidazole in the pretreated particles is (1.5-2): (0.8-1): (0.6-0.8).

[0033] As a preferred solution, the average particle size of the graphite powder is 500-650 nm.

[0034] As a preferred solution, the average particle size of the silicon dioxide is 10-15 nm.

[0035] In the present application, the corrosion resistance, water resistance, stability, aging resistance and wear resistance of the coating can be effectively increased by adding the above-mentioned modified filler. The added modified filler can form a composite particle structure with graphite powder as the matrix, which is embedded on the surface of the framework particles and filled with silica particles. The existence of this structure can greatly enhance the intermolecular effect of the modified filler on the resin material in the present application, greatly enhance the spreading effect of the modified filler in the film-forming system, and then play a good surface structure construction in the formation process of the coating, and then greatly reduce the formation efficiency of the hydration layer on the surface of the coating through the extremely low surface energy of the framework particles and the rougher surface structure, prevent the connection and connection of a small part of the agglomerated water area, and then obtain an excellent surface water repellent effect, and can greatly reduce the penetration and corrosion effect of the aqueous corrosive solution on the coating, reduce the efficiency of its active groups and molecules entering the internal system of the coating, and greatly increase the penetration resistance, and then obtain good stability, water resistance and aging corrosion resistance.

[0036] As a preferred solution, the solvent is a combination of deionized water and short-chain alcohol.

[0037] As a preferred solution, the mass ratio of the deionized water to the short-chain alcohol is (3-5): (1-1.5).

[0038] As a preferred solution, the mass ratio of the deionized water to the short-chain alcohol is 4:1.

[0039] As a preferred solution, the short-chain alcohol is at least one of ethanol, ethylene glycol, propylene glycol, dipropylene glycol, 1,2-pentanediol, and 1,3-butanediol.

[0040] As a preferred solution, the short-chain alcohol is ethylene glycol.

[0041] The second aspect of the present application provides a method for preparing the above-mentioned environmentally friendly and highly anti-corrosion zinc-aluminum coating for metal components, which specifically includes the following steps: S1: Mix zinc powder and aluminum powder and sieve to remove impurities, maintaining a purity of ≥99.5%, then add resin material, modified filler, wetting agent and dispersant and mix and stir evenly: S2: Then add solvent and defoaming agent and continue to stir evenly. After stirring is completed, let it stand naturally to defoam for 0.5~1h, and finally remove the undispersed agglomerated particles by filtering to obtain the coating.

[0042] The beneficial effects of this application are:

[0043] 1. The environmentally friendly and highly anti-corrosion zinc-aluminum coating for metal components provided in this application has good anti-corrosion and environmental protection properties, and at the same time retains excellent coating waterproofing, high temperature / chemical stability, aging resistance, wear resistance and other properties, and achieves good comprehensive performance, effectively meeting the performance requirements of existing metal component products for zinc-aluminum coatings, and has very excellent application prospects.

[0044] 2. The environmentally friendly and highly anti-corrosion zinc-aluminum coating for metal components provided in the present application, wherein the modified epoxy resin added therein can not only effectively improve the construction speed of the coating film layer, but also effectively improve the corrosion resistance, stability and water resistance; the modified epoxy resin can effectively form a strong intermolecular effect on the modified filler during the construction process of the coating, thereby serving as its excellent flow carrier, and can also greatly enhance the position stability of the modified filler in the coating system by intermolecular action after the coating is cured, thereby effectively ensuring the overall stability and water resistance, and the modified epoxy resin can react with the amino group of the siloxane while forming a polyhydroxy system, thereby forming a good hydrogen bonding effect inside the coating system, thereby strengthening the overall coating density and internal connection strength, thereby obtaining better and excellent comprehensive performance.

[0045] 3. The environmentally friendly and highly anti-corrosion zinc-aluminum coating for metal components provided in the present application, the added modified filler can form a composite particle structure with graphite powder as the matrix, the surface of the framework particles is embedded, and the silica particles are filled. The existence of this structure can greatly enhance the intermolecular effect of the modified filler on the resin material in the present application, and greatly enhance the spreading effect of the modified filler in the film-forming system, thereby playing a good role in the construction of the surface structure in the formation process of the coating. The extremely low surface energy of the framework particles and the rougher surface structure greatly reduce the formation efficiency of the hydration layer on the surface of the coating, prevent the connection and connection of a small part of the agglomerated water area, thereby obtaining an excellent surface water-repellent effect, and can thereby greatly reduce the penetration and corrosion effect of aqueous corrosive solutions on the coating, reduce the efficiency of its active groups and molecules entering the internal system of the coating, and greatly increase the penetration resistance, thereby obtaining good stability, waterproofness, and aging corrosion resistance. DETAILED DESCRIPTION

[0046] The following will further explain and demonstrate the technical solutions in the above invention content of this application in the form of specific implementation schemes. The following embodiments are only practical examples used to illustrate and explain the contents of the technical solutions in the specification, and should not limit the scope of the claims to be protected by this application. All technical products based on the technical solutions described in the invention content of this application should be included in the scope to be protected by this application.

[0047] In the following examples, unless otherwise specified, the raw materials are all commercially available products, or can be prepared by methods well known to those skilled in the art.

[0048] Embodiment 1 of the present invention

[0049] Example 1 The first aspect provides an environmentally friendly, highly anti-corrosion zinc-aluminum coating for metal components. The raw materials are, by mass: 30.5 parts of zinc powder, 14.2 parts of aluminum powder, 9.8 parts of wetting agent, 2.2 parts of dispersant, 17.8 parts of resin material, 0.8 parts of defoaming agent, 14.6 parts of modified filler, and 50 parts of solvent.

[0050] The zinc powder is in the form of flakes, the thickness of the flakes is 0.26 μm, and the average diameter of the flakes is 9.5 μm.

[0051] The aluminum powder is flaky aluminum powder, the thickness of the flaky aluminum powder is 0.18 μm, and the average diameter of the flaky aluminum powder is 13.8 μm.

[0052] The wetting agent is a composition of coconut oil-based betaine and cetearyl alcohol polyoxyethylene ether, and the mass ratio of the two is 1:3.2.

[0053] Cetearyl alcohol polyoxyethylene ether was purchased from the O-8 model product sold by Hai'an Guoyun Chemical; cocoyl betaine was purchased from the CAB35 cocoamidopropyl betaine product sold by Shandong Baihua Chemical Co., Ltd.

[0054] The dispersant was polyethylene glycol 1000.

[0055] The resin material is a modified epoxy resin, and the preparation method of the modified epoxy resin includes the following steps, calculated by mass: S1: decompressing and dehydrating the epoxy resin at 120°C for 3 hours to ensure that the moisture content of the epoxy resin is ≤0.3wt%, and cooling to obtain the dehydrated epoxy resin; S2: after decompressing and dehydrating, placing 22.6 parts of epoxy resin in 250 parts of toluene solvent, heating to 80°C and stirring evenly, then adding 1.4 parts of 3-aminopropylmethyldiethoxysilane, 4.4 parts of glutaric anhydride and 0.22 parts of triethylamine, heating to 95°C and reacting for 4 hours; S3: after the reaction is completed, adding 2.4 parts of amylopectin and 0.66 parts of vinyltriethoxysilane, cooling to 62°C and keeping warm for 2 hours, and after the reaction is completed, naturally cooling the product to room temperature and centrifuging, washing with deionized water 3 times, and then drying in a vacuum oven at 70°C to constant weight to obtain the product.

[0056] The epoxy resin is a bisphenol A epoxy resin with an epoxy equivalent of 182 g / eq, and is purchased from Hanson, USA, under the model EPON 828.

[0057] The amylopectin was purchased from Wuhan Lanabai Company, with a branched content of 73.2%.

[0058] The viscosity of the modified epoxy resin is 4800 cPs at 25°C.

[0059] The defoamer is silicone defoamer BYK-016.

[0060] The preparation method of the modified filler includes the following steps, calculated by mass: S1: 3.1 parts of graphite and 0.48 parts of silicon dioxide are mixed and added to 100 parts of DMF solvent, 1.4 parts of succinic anhydride, 0.34 parts of monoalkoxy titanate coupling agent KR-TTS and 0.1 parts of triethylamine are added, and the temperature is raised to 65°C and kept warm for 3 hours; S2: The S1 product is centrifuged and filtered to obtain pretreated particles, 1.8 parts of the pretreated particles are washed and dried, and then added to 60 parts of toluene solvent, and 0.9 parts of zinc nitrate are added at the same time, the temperature is raised to 55°C, and stirred at 120rpm for 40 minutes, during which 0.65 parts of toluene solution of dimethylimidazole (20 parts in total) are added, and then the temperature is raised to 65°C and stirred at 45rpm for 2.8 hours. After the reaction is completed, the product is centrifuged and filtered, and the product is washed with deionized water and vacuum dried to obtain.

[0061] The average particle size of graphite powder is 566 nm, and the corresponding size product was purchased from Shijiazhuang Baijiang Mineral Products Co., Ltd.

[0062] The average particle size of silica was 12.6 nm.

[0063] The solvent is a composition of deionized water and ethylene glycol, and the mass ratio of the two is 4:1.

[0064] The second aspect of this embodiment provides a method for preparing the above-mentioned environmentally friendly and highly anti-corrosion zinc-aluminum coating for metal components, which specifically includes the following steps: S1: Mix zinc powder and aluminum powder and sieve to remove impurities, maintaining a purity of ≥99.5%, then add resin material, modified filler, wetting agent and dispersant and mix and stir evenly: S2: Then add solvent and defoaming agent and continue to stir evenly. After stirring, let it stand naturally for 1 hour to defoam, and finally remove the undispersed agglomerated particles by filtering.

[0065] Embodiment 2 of the present invention

[0066] Example 2 The first aspect provides an environmentally friendly, highly anti-corrosion zinc-aluminum coating for metal components. The raw materials are, by mass: 34.5 parts of zinc powder, 12.5 parts of aluminum powder, 7.6 parts of wetting agent, 2.2 parts of dispersant, 15.5 parts of resin material, 0.8 parts of defoaming agent, 11.2 parts of modified filler, and 55 parts of solvent.

[0067] The zinc powder is in the form of flakes, the thickness of the flakes is 0.26 μm, and the average diameter of the flakes is 9.5 μm.

[0068] The aluminum powder is flaky aluminum powder, the thickness of the flaky aluminum powder is 0.18 μm, and the average diameter of the flaky aluminum powder is 13.8 μm.

[0069] The wetting agent is a composition of coconut oil-based betaine and cetearyl alcohol polyoxyethylene ether, and the mass ratio of the two is 1:3.2.

[0070] Cetearyl alcohol polyoxyethylene ether was purchased from the O-8 model product sold by Hai'an Guoyun Chemical; cocoyl betaine was purchased from the CAB35 cocoamidopropyl betaine product sold by Shandong Baihua Chemical Co., Ltd.

[0071] The dispersant was polyethylene glycol 1000.

[0072] The resin material is a modified epoxy resin, and the preparation method of the modified epoxy resin includes the following steps, calculated by mass: S1: decompressing and dehydrating the epoxy resin at 120°C for 3 hours to ensure that the moisture content of the epoxy resin is ≤0.3wt%, and cooling to obtain the dehydrated epoxy resin; S2: after decompressing and dehydrating, placing 22.6 parts of epoxy resin in 250 parts of toluene solvent, heating to 80°C and stirring evenly, then adding 1.4 parts of 3-aminopropylmethyldiethoxysilane, 4.4 parts of glutaric anhydride and 0.22 parts of triethylamine, heating to 95°C and reacting for 4 hours; S3: after the reaction is completed, adding 2.4 parts of amylopectin and 0.66 parts of vinyltriethoxysilane, cooling to 62°C and keeping warm for 2 hours, and after the reaction is completed, naturally cooling the product to room temperature and centrifuging, washing with deionized water 3 times, and then drying in a vacuum oven at 70°C to constant weight to obtain the product.

[0073] The epoxy resin is a bisphenol A epoxy resin with an epoxy equivalent of 182 g / eq, and is purchased from Hanson, USA, under the model EPON 828.

[0074] The amylopectin was purchased from Wuhan Lanabai Company, with a branched content of 73.2%.

[0075] The viscosity of the modified epoxy resin is 4800 cPs at 25°C.

[0076] The defoamer is silicone defoamer BYK-016.

[0077] The preparation method of the modified filler includes the following steps, calculated by mass: S1: 3.1 parts of graphite and 0.48 parts of silicon dioxide are mixed and added to 100 parts of DMF solvent, 1.4 parts of succinic anhydride, 0.34 parts of monoalkoxy titanate coupling agent KR-TTS and 0.1 parts of triethylamine are added, and the temperature is raised to 65°C and kept warm for 3 hours; S2: The S1 product is centrifuged and filtered to obtain pretreated particles, 1.8 parts of the pretreated particles are washed and dried, and then added to 60 parts of toluene solvent, and 0.9 parts of zinc nitrate are added at the same time, the temperature is raised to 55°C, and stirred at 120rpm for 40 minutes, during which 0.65 parts of toluene solution of dimethylimidazole (20 parts in total) are added, and then the temperature is raised to 65°C and stirred at 45rpm for 2.8 hours. After the reaction is completed, the product is centrifuged and filtered, and the product is washed with deionized water and vacuum dried to obtain.

[0078] The average particle size of graphite powder is 566 nm, and the corresponding size product was purchased from Shijiazhuang Baijiang Mineral Products Co., Ltd.

[0079] The average particle size of silica was 12.6 nm.

[0080] The solvent is a composition of deionized water and ethylene glycol, and the mass ratio of the two is 4:1.

[0081] The second aspect of this embodiment provides a method for preparing the above-mentioned environmentally friendly and highly anti-corrosion zinc-aluminum coating for metal components, which specifically includes the following steps: S1: Mix zinc powder and aluminum powder and sieve to remove impurities, maintaining a purity of ≥99.5%, then add resin material, modified filler, wetting agent and dispersant and mix and stir evenly: S2: Then add solvent and defoaming agent and continue to stir evenly. After stirring, let it stand naturally for 1 hour to defoam, and finally remove the undispersed agglomerated particles by filtering.

[0082] Comparative Example 1 of the present invention

[0083] The specific implementation method of this comparative example is basically the same as that of Example 1, with the only difference being that the environmentally friendly high-corrosion resistant zinc-aluminum coating specially used for metal components, in parts by mass, comprises the following raw materials: 30.5 parts of zinc powder, 14.2 parts of aluminum powder, 9.8 parts of wetting agent, 2.2 parts of dispersant, 17.8 parts of resin material, 0.8 parts of defoaming agent, 5.5 parts of modified filler and 50 parts of solvent.

[0084] Comparative Example 2 of the present invention

[0085] The specific implementation method of this comparative example is basically the same as that of Example 1, with the only difference being that the environmentally friendly high-corrosion resistant zinc-aluminum coating specially used for metal components has the following raw materials, in parts by mass: 30.5 parts of zinc powder, 14.2 parts of aluminum powder, 9.8 parts of wetting agent, 2.2 parts of dispersant, 12.4 parts of resin material, 0.8 parts of defoaming agent, 28.6 parts of modified filler, and 50 parts of solvent.

[0086] Comparative Example 3 of the present invention

[0087] The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation method of the modified epoxy resin comprises the following steps, in parts by mass: S1: dehydrating the epoxy resin under reduced pressure for 3 hours at 120°C to ensure that the moisture content of the epoxy resin is ≤0.3wt%, and cooling to obtain the dehydrated epoxy resin; S2: after the dehydration is completed, 10.5 parts of the epoxy resin are placed in 250 parts of toluene solvent, heated to 80°C and stirred evenly, then 3 parts of 3-aminopropylmethyldiethoxysilane, 6.5 parts of glutaric anhydride and 0.48 parts of triethylamine are added, and the temperature is raised to 95°C for reaction for 4 hours; S3: after the reaction is completed, 2.4 parts of amylopectin and 0.66 parts of vinyltriethoxysilane are added, and the temperature is reduced to 62°C and kept warm for 2 hours. After the reaction is completed, the product is naturally cooled to room temperature and centrifuged, washed 3 times with deionized water, and then dried in a vacuum oven at 70°C to constant weight.

[0088] Comparative Example 4 of the present invention

[0089] The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation method of the modified epoxy resin comprises the following steps, in parts by mass: S1: dehydrating the epoxy resin under reduced pressure for 3 hours at 120°C to ensure that the moisture content of the epoxy resin is ≤0.3wt%, and cooling to obtain the dehydrated epoxy resin; S2: after the dehydration is completed, 22.6 parts of the epoxy resin are placed in 250 parts of toluene solvent, heated to 80°C and stirred evenly, then 1.4 parts of 3-aminopropylmethyldiethoxysilane, 4.4 parts of glutaric anhydride and 0.22 parts of triethylamine are added, and the temperature is raised to 95°C for reaction for 4 hours; S3: after the reaction is completed, 0.5 parts of amylopectin and 0.15 parts of vinyltriethoxysilane are added, and the temperature is lowered to 62°C and kept warm for 2 hours. After the reaction is completed, the product is naturally cooled to room temperature and centrifuged, washed 3 times with deionized water, and then dried in a vacuum oven at 70°C to constant weight.

[0090] Comparative Example 5 of the present invention

[0091] The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation method of the modified filler comprises the following steps, calculated by mass: S1: 3.1 parts of graphite and 0.48 parts of silicon dioxide are mixed and added to 100 parts of DMF solvent, 1.4 parts of succinic anhydride, 0.34 parts of monoalkoxy titanate coupling agent KR-TTS and 0.1 parts of triethylamine are added, and the temperature is raised to 65°C and kept warm for 3 hours; S2: the S1 product is centrifuged to obtain pretreated particles, 4.5 parts of the pretreated particles are washed and dried, and then added to 100 parts of toluene solvent, and 0.5 parts of zinc nitrate are added at the same time, the temperature is raised to 55°C, and stirred at 120rpm for 40min, during which 0.32 parts of toluene solution of dimethylimidazole (a total of 15 parts) are added, and then the temperature is raised to 65°C and stirred at 45rpm for 2.8h. After the reaction is completed, the product is centrifuged and filtered, and the product is washed with deionized water and vacuum dried to obtain.

[0092] Comparative Example 6 of the present invention

[0093] The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation method of the modified filler comprises the following steps, calculated by mass: S1: 3.1 parts of graphite and 0.11 parts of silicon dioxide are mixed and added to 100 parts of DMF solvent, 0.8 parts of succinic anhydride, 0.15 parts of monoalkoxy titanate coupling agent KR-TTS and 0.05 parts of triethylamine are added, and the temperature is raised to 65°C and kept warm for 3 hours; S2: the S1 product is centrifuged to obtain pretreated particles, 1.8 parts of the pretreated particles are washed and dried, and then added to 60 parts of toluene solvent, and 0.9 parts of zinc nitrate are added at the same time, the temperature is raised to 55°C, and stirred at 120rpm for 40min, during which 0.65 parts of toluene solution of dimethylimidazole (20 parts in total) are added, and then the temperature is raised to 65°C and stirred at 45rpm for 2.8h. After the reaction is completed, the product is centrifuged and filtered, and the product is washed with deionized water and vacuum dried to obtain.

[0094] Comparative Example 7 of the present invention

[0095] The specific implementation of this comparative example is basically the same as that of Example 1, except that: the average particle size of the graphite powder is 880 nm, and the corresponding size product is purchased from Shijiazhuang Baijiang Mineral Products Co., Ltd.; the average particle size of the silicon dioxide is 35 nm.

[0096] Performance Evaluation

[0097] Salt spray resistance test: The coatings obtained from the coatings prepared in the embodiments and comparative examples were subjected to a salt spray resistance test. The coating thickness was 100 μm, the test environment temperature was 35 ± 2 ° C, the humidity was 98 ± 2%, the test solution was 5 wt% NaCl solution, and the test time was 400 h. After the test, the coating was observed for corrosion, shedding, cracking, and blistering. If so, it was recorded as unqualified, otherwise it was qualified. 50 samples were tested in each group, and the qualified rate was recorded in Table 1.

[0098] Aging resistance test: The coatings obtained from the coatings prepared in the embodiments and comparative examples were subjected to an aging resistance test in a constant temperature and humidity chamber. The coating thickness was 100 μm, the test environment temperature was 65±2°C, and the humidity was 75±2%. After the test, the coating was observed for oxidation, shedding, cracking, and blistering. If so, it was recorded as unqualified, otherwise it was qualified. 50 samples were tested in each group, and the qualified rate was recorded in Table 1.

[0099] Waterproof test: The coatings obtained from the examples and comparative examples were tested for water resistance. The coating thickness was 100 μm. The sessile drop method was used. The test water drop was 2 μL and the test time was 10 s. The test values ​​were the average of 10 tests and recorded in Table 1.

[0100] Abrasion resistance test: The coatings obtained from the coatings prepared in the examples and comparative examples were subjected to abrasion resistance test, with reference to standard GB / T 1768-2006, 1 kg / 1000 r, CS-17 wheel, and the test values ​​were taken as the average of 10 tests and recorded in Table 1.

[0101] Table 1 Performance test results

[0102] Example Salt spray resistance qualified rate (%) Ageing resistance qualified rate (%) Surface water contact angle (°) Wear resistance, 1kg / 1000r, CS-17 wheel (mg) Example 1 100 96 98.5 17.5 Example 2 100 94 96.4 18.2 Comparative Example 1 94 88 79.5 24.4 Comparative Example 2 96 84 91.8 19.2 Comparative Example 3 90 78 85.8 21.6 Comparative Example 4 92 76 86.2 20.6 Comparative Example 5 88 80 86.6 19.8 Comparative Example 6 84 74 85.9 19.3 Comparative Example 7 86 78 90.3 20.5

[0103] It can be seen from the examples and comparative examples of the present application and the data results in Table 1 that Examples 1 and 2 of the present application have obvious advantages over comparative examples 1 to 7 in terms of wear resistance, waterproof performance, corrosion resistance and aging resistance. This is mainly due to the combined effect of the modified fillers, modified epoxy resin materials and other compounding technical solutions specified in the present application. Comparative examples 1 to 7 did not adopt the technical solution specified in the present application, resulting in obvious disadvantages in the above-mentioned performance tests, which further proves the necessity of the technical solution specified in the present application for the technical effect of the present application and solving technical problems.

Claims

1. Environmentally friendly and highly anti-corrosion zinc-aluminum coating for metal components, characterized by: The raw materials are as follows: 20-40 parts of zinc powder, 10-25 parts of aluminum powder, 5-15 parts of wetting agent, 1-3 parts of dispersant, 10-20 parts of resin material, 0.5-1 parts of defoaming agent, 10-15 parts of modified filler, and 40-55 parts of solvent. The mass ratio of the zinc powder, aluminum powder and modified filler is (25-35): (12-18): (11-15); The mass ratio of the wetting agent, the resin material and the modified filler is (6-14): (15-20): (11-15); The zinc powder is flaky zinc powder; the thickness of the flaky zinc powder is 0.2-0.4 μm; the average diameter of the flaky zinc powder is 5-15 μm; The aluminum powder is flaky aluminum powder; the thickness of the flaky aluminum powder is 0.15-0.3 μm; the average diameter of the flaky aluminum powder is 10-20 μm; The resin material is a modified epoxy resin; The preparation method of the modified epoxy resin comprises the following steps: S1: decompressing and dehydrating the epoxy resin for 2-4 hours at 120-125° C. to ensure that the moisture content of the epoxy resin is ≤0.3wt%, and cooling to obtain the dehydrated epoxy resin; S2: after decompressing and dehydrating, placing the epoxy resin in a toluene solvent, heating it to 70-80° C. and stirring evenly, then adding aminosiloxane, glutaric anhydride and triethylamine, heating it to 90-110° C. and reacting it for 3-5 hours; S3: after the reaction is completed, adding amylopectin and a silane coupling agent, cooling it to 60-65° C. and keeping it warm for 1.5-2 hours, and after the reaction is completed, naturally cooling the product to room temperature and centrifuging it, washing it with deionized water for 2-3 times, and then drying it in a vacuum oven to constant weight to obtain the product; The mass ratio of the epoxy resin, aminosiloxane, glutaric anhydride and triethylamine is (20-25): (1-1.5): (3-5): (0.2-0.4); The preparation method of the modified filler comprises the following steps: S1: adding a mixture of graphite and silicon dioxide to a DMF solvent, adding succinic anhydride, a titanate coupling agent and triethylamine, heating to 60-65° C. and keeping the temperature for 3-3.5 hours; S2: centrifugally filtering the S1 product to obtain pretreated particles, washing and drying the pretreated particles, adding them to a toluene solvent, and adding zinc nitrate at the same time, heating to 50-55° C., stirring at a speed of 100-120 rpm for 30-40 minutes, adding a toluene solution of dimethylimidazole during the stirring, and then heating to 60-65° C. and stirring at a speed of 40-60 rpm for 2.5-3.5 hours. After the reaction is completed, centrifugally filtering, washing the product with deionized water and vacuum drying, the product is obtained; The mass ratio of the graphite, silicon dioxide, succinic anhydride, titanate coupling agent and triethylamine is (3-3.5): (0.4-0.6): (1-1.5): (0.3-0.4): (0.05-0.15); The average particle size of the graphite powder is 500-650 nm; The average particle size of the silicon dioxide is 10-15 nm.

2. The environmentally friendly high anti-corrosion zinc-aluminum coating for metal components according to claim 1 is characterized by: The wetting agent is a composition of coconut oil-based betaine and cetearyl alcohol polyoxyethylene ether; the mass ratio of the coconut oil-based betaine and cetearyl alcohol polyoxyethylene ether is (1-1.5): (3-4).

3. The environmentally friendly high corrosion resistance zinc-aluminum coating for metal components according to claim 2 is characterized by: The dispersant is at least one of polyethylene glycol, polycarboxylate, polyamide wax and modified siloxane.

4. The environmentally friendly high corrosion resistant zinc-aluminum coating for metal components according to claim 3 is characterized by: The aminosiloxane is γ-aminopropyltriethoxysilane or 3-aminopropylmethyldiethoxysilane; the epoxy resin is bisphenol A epoxy resin; the epoxy equivalent of the bisphenol A epoxy resin is 160-190 g / eq.

5. The environmentally friendly high anti-corrosion zinc-aluminum coating for metal components according to claim 4 is characterized in that: The viscosity of the modified epoxy resin is 3000-6000 cPs at 25°C.

6. The environmentally friendly high anti-corrosion zinc-aluminum coating for metal components according to claim 5 is characterized by: The solvent is a composition of deionized water and short-chain alcohol; the mass ratio of the deionized water to the short-chain alcohol is (3-5): (1-1.5).

7. The environmentally friendly high anti-corrosion zinc-aluminum coating for metal components according to claim 6 is characterized by: The short-chain alcohol is at least one of ethanol, ethylene glycol, propylene glycol, dipropylene glycol, 1,2-pentanediol, and 1,3-butanediol.

8. A method for preparing the environmentally friendly high corrosion protection zinc-aluminum coating for metal components according to any one of claims 1 to 7, characterized in that: The specific steps include: S1: Mix zinc powder and aluminum powder and sieve to remove impurities, maintain purity ≥ 99.5%, then add resin material, modified filler, wetting agent and dispersant and mix and stir evenly: S2: Then add solvent and defoaming agent and continue to stir evenly. After stirring, let it stand naturally to defoam for 0.5~1h, and finally remove the undispersed agglomerated particles by filtration.